Citizen participation in the municipal planning process in Portugal - Ana Júlia Pinto (On the W@terfront, 2011)
Analysing the citizen participation developed within the territorial planning processes, in Portugal, we found numerous failures, mainly because participation is limited to the periods established by the Portuguese law, which are clearly insufficient (in the decision of beginning the plan and a period of public discussion when the plan is already fully developed), or because the population is burdened with numerous participatory processes that overlap, most often without producing visible results, leading to the discrediting of citizens from this type of processes . Nevertheless, despite the negative experiences, there are also good practices in the development of citizen participation processes that truly follow up all the urban projects development stages. Most of these cases are small-scale urban interventions, claimed by the population, giving rise to projects that are developed together with the citizens. The urban planning projects including strong citizen participation strategies show great advantages over the others, once they fosters the population “empowerment”, promoting greater involvement by citizens in the processes of urban transformation and hence a greater level of acceptance and satisfaction with the urban interventions undertaken. On the other hand, the involvement of the population also allows a greater and better understanding of the intervention area characteristics, allowing a better adaptation of projects / plans to the physical and socio-economic reality that they intend to serve. Given the remarkable advantages in developing processes of citizen participation able to monitor the urban interventions, it seems evident the need to build real processes of citizen participation, which go beyond the periods provided by law. Instead, the citizen participation processes should go together with the development of a plan or urban design (since the decision of making the plan / project to its formalization and subsequent implementation), and be adapted to the specificities of each case and reality. Therefore, in this work we analyse the challenges currently faced by the implementation of citizen participation processes in the development of urban interventions, in Portugal. Through this analysis we try to establish guidelines to build citizen participation processes able to improve the development of urban interventions in different territorial scales.